Analisis Disiplin Kerja Dalam Upaya Meningkatkan Kinerja Karyawan Di Pt Pegadaian Tanjung Uban - Dwi Putri, Retno; Iranita, Iranita; Jalal, Abdul (Bahtera Inovasi, 2023)
This study aims to: 1) To find out what causes employees to be less disciplined in working at PT Pegadaian Tanjung Uban, 2) To find out how efforts are made to improve employee performance at PT Pegadaian Tanjung Uban, 3) To find out what efforts are made in improving discipline in working at PT Pegadaian Tanjung Uban. The qualitative descriptive method was applied in this investigation. Data is collected in the field via observation, interview, and direct observation methods, therefore the data used are primary data and secondary data. This research looked at, NVIVO 12 Pro software was assisted in analyzing data. According to the findings of this study, the causes of workers are less disciplined due to lack of leadership firmness, lack of supervision, habits, quiet customer and absence of work. Meanwhile, efforts are made to improve employee performance that has a correlation value of 0.806178, namely at the work appraisal and work evaluation nodes. Furthermore, efforts to improve discipline in work that have a correlation value above 0.5, namely in nodes punishment and job training with a value of 0.921866. It is hoped that PT Pegadaian can continue to improve employee performance and employee discipline at work.